A Comparative Study of the Topographical State of Parts of the Lake Floor of 16 Tishreen Dam in Lattakia - بوبو معن (Latakia University Journal -Engineering Sciences Series, 2020)
The majority of water studies focus on dams and their lakes, in searching for the quantities of sediments received through the different waterways to those lakes in order to search for their true values of storage capacity; but do the values of these sediments change from one area to another in the lake? What is the situation for other areas that do not have waterways? especially after dry seasons that cause the disintegration of their soil and make it vulnerable to erosion or drift factors with water torrents. This research is based on a comparative study between two areas of the 16 Tishreen Dam lake in Lattakia: one of which is not fed by waterways, and the other is located at the estuary of Al-Kabir al-Shamali river and its tributaries to the lake (the foot of the lake). Three periods of time were compared: before the dam was built, in the autumn of a dry year of 2014, and in the rainy spring of 2017. The research concluded results that the first region has been exposed to erosion of its banks or bottom, a process that did not stop over time despite its low frequency, while in the foot region of the lake there were sedimentation processes in general, despite the registration of some of the drift sites, and it also determined the sedimentation and drift quantities in both regions.